Portscapes - Havenbedrijf Rotterdam (Rotterdam : Port of Rotterdam Authority, Amsterdam : SKOR (Foundation Art and Public Space)., 2009)
Almarcegui, Lara; Barnas, Maria; Van Der Pol, Bik; Dibbets, Jan; Dijkman, Marjolijn; Fucking Good Art; Halperin, Ilana; Christina Hemauer & Roman Keller; Miessen, Markus; Satorre, Jorge; Schabus, Hans
Portscapes is a series of newly commissioned art projects in the context of the construction of Maasvlakte 2
Includes 7 booklets, 4 leaflets (including box contents), 2 postcards, 1 DVD, 1 CD and 1 poster in box
Nederlands, Engels
boek